Controller design and performance evaluation for liquid desiccant dehumidification system - Chen, Yushan (2016)
Recently, liquid desiccant dehumidification system has emerged as a cost-effective and environmental-friendly method of cooling and dehumidification of air. The object of the project is to investigate the operation of the liquid desiccant dehumidification system; focus on evaluation for the performance of the regenerator. Experiment data were collected to study the mass transfer process in the regenerator. Properties change of the desiccant solution were discussed in this paper and an effective model to describe the concentration variation of desiccant solution with respect to liquid temperature and difference in inlet and outlet absolute humidity of regenerating air was proposed and verified. By applying Levenberg-Marquardt method, the parameters to determine the mass flux for this liquid desiccant dehumidification system could be determined. Simulated results established based on the proposed model were compared with the experiment data. The results shows an agreement of the simulated results and collected experiment data within an acceptable error range. Thus, the proposed model is considered usable to predict the concentration of desiccant solution in the regenerator for further experiments.